New Interpretative Approaches to the Study of Slavic Paganism. The Case of a Pseudo-Chrysostomian Homily in East Slavic - Torres Prieto, Susana (Brepols, 2017)
The Slavic tradition was rich in translating and adapting the homilies of John Chrysostom, and his name was used to endow newly-composed texts with authority. On the homilies addressing the problem of pagan practices, Slavic monks, while refraining from changing or expurgating the received texts, eventually added descriptions of local practices to be condemned in the same terms that Chrysostom condemned the practices in Constantinople. This particular way of ‘composing’ (by adding or changing the order of textual units to a given text) had two main consequences in Slavic medieval letters. On the one hand, Chrysostom was probably the most popular Church Father in Slavic due to the extensive copying, albeit hardly ever faithfully, of his homilies; on the other, studies on Slavic paganism tended to take at face value the whole content of such homilies without discerning which parts were truly Chrysostomian, i.e., describing Constantinopolitan practices, and which were solely Slavic, thus attributing certain rituals to Slavic paganism that were probably never practiced among the Slavs. The present article aims, firstly, at describing the adaptation process of Chrysostomian homiletics in Slavic by using a case-study, and, secondly, at evaluating the role such adaptations played in the definition of Early Christianity, as well as in the study and misinterpretation of Slavic paganism from the nineteenth century onwards.
Keywords: 55 Historia::5504 Historia por épocas::5504.03 Historia medieval; ODS 11 - Ciudades y comunidades sostenibles